The use of the DPA concept and the formulation of sanctions as a reform of state loss recovery in cases of corruption by corporations - Muhammad Syafiq Wafi; Abdullah Widy As-Shidiq; Rifki Yustisio (Universitas Negeri Yogyakarta, 2025)
In the development of the modern justice system, criminalization of corporations has undergone significant changes, one of which is through the Deferred Prosecution Agreement (DPA) approach. This approach reflects a paradigm shift in criminal law enforcement involving three principles of justice: corrective justice, which focuses on the perpetrator; rehabilitative justice, which emphasizes the role of the victim; and restorative justice, which promotes the restoration of relations between the two parties. This research uses normative juridical methods and empirical studies, focusing on anti-corruption handling and asset recovery. The findings of the study show that the DPA provides an opportunity for the prosecution of the corporation to be suspended. Through this concept, lawsuits can be replaced with other forms of liability that are in accordance with the regulations that govern the reimbursement of claims. From an academic perspective, this study aims to formulate a model of the mechanism for preventing corruption crimes by corporations by utilizing DPA. This is expected to be part of legal reform in recovering state losses arising from corporate crimes.